Proteomic analysis of Toraya buffalo seminal plasma and sperm: uncovering insights to optimize reproductive success - Maulana, Tulus; Said, Syahruddin; Arifiantini, Raden Iis; Jakaria, Jakaria; Gunawan, Asep (Frontiers in Veterinary Science, 2025)
The characterization of sperm and seminal plasma proteins is essential for understanding bull fertility and optimizing reproductive success in buffalo bulls. Despite its importance, the reproductive proteomic of Toraya buffalo, an indigenous breed in Indonesia, remains largely unexplored. This study aimed to examine the seminal plasma and sperm proteins of Toraya buffalo to uncover those critical for reproductive functions. Semen samples were collected from eight Toraya buffalo bulls aged 4 to 10 years. Protein profiling was performed using one-dimensional sodium dodecyl sulfate-polyacrylamide gel electrophoresis (1D-SDS-PAGE), followed by in-gel digestion and liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis. Bioinformatics tools, including UniProt, PANTHER, DAVID, and STRING, were utilized to identify and annotate the detected proteins. This study successfully identified four key reproductive proteins: ADAM32 in seminal plasma and ZPBP, SPACA3, and CCDC136 in sperm. These proteins are essential for sperm motility, energy production, and acrosome formation, which are critical processes for fertilization. Additionally, many identified proteins were associated with metabolic pathways, particularly the tricarboxylic acid (TCA) cycle, which plays a fundamental role in energy supply for sperm function. In conclusion, this study offers the first comprehensive proteomic identification of seminal plasma and sperm proteins associated with reproductive functions in the Toraya buffalo. The findings highlight the presence of key proteins in sperm, including ZPBP, SPACA3, and CCDC136, as well as the identification of ADAM32 in seminal plasma, contributing to a deeper understanding of buffalo reproductive biology.